2012
DOI: 10.1103/physrevlett.109.248303
|View full text |Cite
|
Sign up to set email alerts
|

Shear Banding in an F-Actin Solution

Abstract: We report herein the first evidence that an F-actin solution shows shear banding, which is characterized by the spontaneous separation of homogeneous shear flow into two macroscopic domains of different definite shear rates. The constant shear stress observed in the F-actin solution is explained by the banded flow with volume fractions that obey the lever rule. Nonhomogenous reversible flows were observed in the F-actin solution with respect to upward and downward changes in the shear rate. This is the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…In the recent study, it is reported that a fibrous actin solution exhibits shear thinning or shear banding property [26]. Although the mechanism of that behavior on actin solution has not been solved, the similar discussion may be applicable to the present results, i.e., the bipolar myosin thick filament and actin filaments should be forced in parallel to the stream line to reduce friction or entanglement each other, which may inhibit the growth of gelling network.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In the recent study, it is reported that a fibrous actin solution exhibits shear thinning or shear banding property [26]. Although the mechanism of that behavior on actin solution has not been solved, the similar discussion may be applicable to the present results, i.e., the bipolar myosin thick filament and actin filaments should be forced in parallel to the stream line to reduce friction or entanglement each other, which may inhibit the growth of gelling network.…”
Section: Resultssupporting
confidence: 62%
“…For the order estimation of the tension, if viscosity exhibits the same value of water, the shear strength [s −1 ] results in ∼ 20 µN/M in surface tension, which was one order of magnitude larger than that in Figure 3A. From this order estimation and the fact that the actomyosin viscosity was quite high, e.g., 4.5mPa s in cytoplasmic sol in vivo [25] and ∼100 mPa s in F-action solution [26], it can be supposed that almost all the contractive force of the actomyosin gel was used for deforming own body [27], and the part of the stored elastic energy was relieved from the rupture as the protrusion. In this geometry, Young’s modulus of the inner droplet part has relatively lower value because of the continuous flow, and Young’s modulus of the cortex , where is the thickness of the cortex, which can be assumed to be lower in the early effusion stage: [21].…”
Section: Resultsmentioning
confidence: 91%
“…To understand the intricate roles of the actomyosin cortex in cellular processes, bottom-up or reconstitution approaches with a small number of essential components have been adopted. For example, actin polymerization and depolymerization with actin-related proteins in purified systems [8], the rheological measurements of purified F-actin solution [9], the motor activity of myosin from the perspective of its interaction with actin [10], and single molecule analysis [11] have been examined thus far. As reconstitutions of biomimetic artificial systems, the surfaces of giant unilamellar vesicles [12][13][14][15][16] or beads [17,18] have been utilized frequently to investigate the physicochemical properties of interfacial deformation or symmetry breaking of the surrounding actin cortices.…”
Section: Introductionmentioning
confidence: 99%
“…All fluids have a uniform-flow regime. Shear-banding is found in polymers [8,9], colloids [10,11] and various surfactant phases [12][13][14]. Slip-planes occur in surfactant cubic phases [26] and polymer melts [30,31], and both slip and coexistences are seen in foams [15,32] and colloids [10,11,33].…”
mentioning
confidence: 96%
“…foams, particulate suspensions and smectic liquid crystals) can exhibit coexistence of macroscopic regions with distinct shear rates [8][9][10][11][12][13][14][15]. This phenomenon, known as shear banding, has been explained in terms of various models with non-trivial stress fields [16][17][18][19].…”
mentioning
confidence: 99%